Traumatismos dentários em adolescentes: prevalência e associação com fatores socioeconômicos e consumo de drogas ilícitas e álcool - Kelly Oliva Jorge (2010)
Dental trauma is a serious dental public health problem among Brazilian adolescents. While there are a large number of studies on the prevalence, etiological factors and predisposing factors of dental trauma, there is a lack of broader-scoped approaches investigating social factors, such as socioeconomic status of the family, and the association of dental trauma to illicit drug and alcohol use. A cross-sectional study was carried out, involving a clinical examination by previously calibrated researchers (intra-examiner Kappa = 0.89; inter-examiner kappa = 0.92) and self-administered questionnaires. The sample was made up of 101 adolescents between 15-19 years old, students from public and private schools. The criteria proposed by Andreasen et al. (2007) were used for the classification of dental trauma. The Belo Horizonte Social Vulnerability Index was used for socioeconomic classification. Information on alcohol and illicit drug use was collected using two questionnaires the Alcohol Use Disorders Identification Test (AUDIT) and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), both of which have been validated in Brazil. The prevalence of traumatic dental injury (TDI) was 30.7%. The most common type of injury was enamel fracture (26.7%), followed by enamel and dentin fracture without pulp exposure (3.0%). Falls (19.4%), use of teeth for functions other than eating (16.1%) and the practice of sports (12.9%) were the most frequent etiological factors. Among the participants with TDI, 61.3% were male (p=0.007). A total 44.8% of individuals with an under-privileged socioeconomic status exhibited some type of TDI (p=0.050). There was a high prevalence of adolescents who consume alcoholic beverages (72.3%) and use illicit substances (18.8%). However, no statistically significant associations were found between these variables and the presence of TDI. More socially vulnerable individuals [OR=2.37 (95% CI: 1.01-5.54)] and those with accentuated overjet (> 5mm) [OR=2.32 (95% CI: 0.74-7.27)] had an approximately 2.3-fold greater chance of belong to the group of individuals diagnosed with some type of TDI. In conclusion, the prevalence of dental trauma was high. The same was true regarding alcohol and illicit drug use among the adolescents examined. Socioeconomic factors and gender were significantly associated to dental trauma.